Fabrication and characterisation of ZrO2-reinforced porous mullite ceramics. (17th November 2022) - Ji, Peng; Song, Chenghao; Wu, Yongwan; Deng, Hailiang; Deng, Xiangong; Zhang, Yi; Ding, Xiang; Zhang, Haijun; Ran, Songlin
ABSTRACT: ZrO2 -reinforced porous mullite ceramics were fabricated by a foam-gel casting approach using zircon (ZrSiO4 ) powders and alumina (Al2 O3 ) powders as raw materials. The influence of firing temperature on the phase composition of porous samples was analysed. Based on the analysis results, the effects of a blowing agent on the physical properties, microstructure, mechanical strength and heat conductivity of ZrO2 -reinforced porous mullite samples fired at 1600°C were investigated. In the present study, linear shrinkage, porosity and mean pore size of ZrO2 -reinforced porous mullite ceramics increased, and volume density, mechanical strength and heat conductivity decreased. When the dosage of the blowing agent was 1.0 vol.-%, the flexural strength and compressive strength of ZrO2 -reinforced porous mullite sample with 77.4% porosity respectively reached 3.0 and 10.9 MPa, and their heat conductivity was kept at 0.181 W m −1 K −1 .